تنمية بعض المهارات اللغوية من خلال استراتجية الحواس المتعددة لدى ذوي التخلف العقلي البسيط دراسة ميدانية بالمركز النفسي البيداغوجي شول عطا الله - جرادي أمينة; قوال إيمان; خنفار سامرة (My University, 2021)
The study aimed to reveal the effectivenss of the VAKT multisensory strategy in developing certain language skills of reading and writing in people with simple mental retardation the study sampel mental retardation the study sampel consisted of (9) cases of people having a simple mental retardation and their ages varied from (10-15) years and their ages The mentality from (8-11) years, at the Psychopedagogical Centre " Scholl Atta Allah " of the city of Laghouat and based on the quasi-experimental approach and the application and scale of language skills (reading and writing) for people with mild mental retardation ,prepared by Mr:Others, in addition to the Artoufien budget, the Observation of the interview and the application of the multisensory training program for his companion (bosbaa aicha). And after applying the program, we calculated the differences between the pre and post measure of language skills. The resulte showed that the differences in the mean scores between the are and post measurement in language skills in the total score as follows: There are substantial and statistially significant differences, in favor of the post-measurement, with means that the program improved the children’s performance level of language skills (reading and writing), in other words, a training prgram based on the multisensory startegy is effective. There are substantial and statiscally signiffiacant differnce , in favor f the post-measuremmeent, which means that the program has improved the level of shildren’n preformmance in reading prograem based the multi-sensory startegy is effetive. There are no differences between the arithmetic mean of individual’s scores in the tribal measurement (before they were exposed to the multisensory based program) and the arithmetic mean of their scores in the postmeasurment (after exposure to the prpgram) in writing and it has no statistial signifiation language skills (reading and wirting), multi-sensory strategy, simple mental retardation.